Penilaian Kinerja dan Efektivitas Mesin Extruder PEX150JA pada Produksi Kabel Medium Voltage (MV) dalam Fase Outer Sheathing di PT Sucaco Tbk - wahid, eka nur wahid; Irwanto Irwanto (Fakultas Teknik UMRI, 2024)
This research evaluates the performance and effectiveness of the PEX150JA extruder machine in the medium voltage cable production process during the outer sheathing phase. The performance was measured using the Overall Equipment Effectiveness (OEE) method, which encompasses Availability, Performance, and Quality rates. Data collected over 12 months revealed an average OEE value of 70%, indicating suboptimal performance compared to the global industry standard of 85%. Contributing factors include component wear and operational inefficiencies. The main findings show that the low OEE is caused by issues with Carbon Brush, Bearing, and Heating System. The practical implications of this research emphasize the necessity of implementing scheduled preventive maintenance to reduce failure frequency. Improvements are proposed based on data analysis and Failure Mode and Effect Analysis (FMEA).